Analysis on the perception of quality and the relation to the performance of human capital - Bórquez Tepezano, Brenda; González Espinoza, Mayda; Muñoz del Real, Gloria; Bórquez Tepezano, Brenda; González Espinoza, Mayda; Muñoz del Real, Gloria (Corporación Universitaria Americana, 2020)
This study analyzed the perception of the quality service in relation to the performance of the human capital of the consulting and advisory company Management Systems Institute. An applied research was carried out with a quantitative approach, supported by data collection techniques through an evaluation instrument. The study shows that the main reasons for obtaining a certification are customer satisfaction, positioning of the company itself and recertifications. It is concluded that the evaluation of the service quality that clients perceive for the consulting companies will depend largely on the performance that human resource performs in its activities during the consulting.